Effect of Oil Pollution on the Antioxidant Activity of the Methanolic Extracts of Polluted and Unpolluted Leaves of Hyptis suaveolens (L) - Egwu, H.A.,; Yilwa, V.M.,; Onusiriuka, B.C.,; Dikwa, K.B.; Yelwa, J.M. (UMYU Journal of Microbiology Research)
Hyptis suaveolens (L.) Poit, an aromatic weed known as pignut or daddoya-ta-daji in the Hausa language, has a longstanding history of usage as food and medicine in Kaduna state. This plant is interestingly found thriving in environments with or without oil pollution. In our modern industrial society, it's practically inevitable that these medicinal plants come in contact with oil contamination. This is largely because oil pipelines, often aged and susceptible to corrosion or illicit activities leading to leakages, are scattered across urban and rural settlements, influencing the plants' phytochemical composition. This study is focused on examining if oil pollution alters the antioxidant activity of this plant. An evaluation of the antioxidant properties of methanol extracts from Hyptis suaveolens (L.) leaves, both from polluted and unpolluted areas, was carried out using the 2,2-Diphenyl-1-Picrylhydrazyl-hydrate (DPPH) free radical scavenging assay. The outcomes showed that the extracts have significant (p < 0.05) concentration-dependent antioxidant activity. Yet, the unpolluted H. suaveolens leaves' methanol extract exhibited superior DPPH radical scavenging action compared to the extract from the polluted leaves. The median inhibitory concentrations (IC50) for the polluted and unpolluted leaves' methanol extracts were 35 µg/ml and 20 µg/ml respectively. Therefore, the contamination had a detrimental impact on the plant extract's antioxidant capacity.